INCORPORATING A COGNITIVE LINGUISTICS APPROACH TO THE TEACHING OF A SELECTION OF FIGURATIVE IDIOMS IN EFL CONTEXT - Dzung Trung Dang (University of Kuningan, 2013)
Abstract:Â Prodromou (2003: 43) states that â€œthe way for a student of English to become more fluent in the language is not only to have a good command of grammar and vocabulary but also a good command of the â€˜idiom principleâ€™ and there is â€œthe need for idiomatic competence is precisely what linguists propose for the non-native speakerâ€. In addition, research shows that idioms are among the biggest challenge for EFL/ESL learners. The aim of this paper is to shed some light on ways to deal with a selection of figurative idioms by employing a CL perspective and to suggest some pedagogical implications. The paper attempts to examine a small number of Vietnamese EFL learners in the use of a non CL and a CL activity to evaluate its effectiveness and learning gains. The results could be used to further explore the use of CL to the teaching of idioms.Key words: cognitive linguistics, figurative idioms, corporaÂ